The Relationship Between Job Satisfaction and Work Motivation with Employee Productivity at UD. Hidayah - Khasanah, Muthi’atul; Al Qusaeri , Muammar Afif; Khasbulloh , M. Wahab; Wiliyanto, Wiliyanto (CV. Civiliza Publishing, 2025)
This study aims to examine the relationship between job satisfaction and work motivation with employee productivity at UD. Hidayah. The background of this research is based on the important role of these two factors in improving labor effectiveness and productivity in order to achieve company objectives. The research approach employed was quantitative, using questionnaires as the data collection tool, distributed to respondents according to the predetermined population. The data obtained from the questionnaires were then analyzed using multiple regression techniques to determine the relationship and influence among variables. The results of the analysis revealed that job satisfaction plays a crucial role by fostering various positive aspects, such as increasing employee productivity and engagement, reducing turnover, attracting qualified talent, building a positive work culture, and even contributing to broader economic stability. Work motivation, whether driven by internal or external factors, was also shown to have a significant and beneficial impact on improving employee performance productivity. When both aspects work together, motivation and job satisfaction have been proven to significantly enhance employee performance productivity.